We are watching : a novel - Gaylin, Alison (William Morrow, an imprint of HarperCollins Publishers, 2025)
"A single mother is desperate to protect her family as they are targeted by a group of violent conspiracy theorists in this riveting and all too plausible thriller from USA Today bestselling author Alison Gaylin. Meg Russo was behind the wheel when it happened. She and her husband Justin were driving their daughter Lily to college, the family celebrating the eighteen-year-old's future. Then a car sidled up beside them, the young men inside it behaving erratically. The Russos' car went off the road, and Justin didn't survive the accident. Four months later, Meg works to distract herself from her grief, reopening her small local bookstore. But soon after returning to work, bizarre messages and visitors begin to arrive, with strangers threatening Meg and vandalizing the store. They are obsessed with a young adult novel tiled The Prophesy, which was published 20 years earlier. An online group of believers are convinced the book predicted a plague, and social media posts link it to Satanism. People are sure it heralds the apocalypse. These conspiracy theorists vow to seek revenge on its author... Meg. As the threats turn more violent, Meg begins to suspect that Justin's death may not have been an accident. To find answers and save herself and Lily, she must get to the root of the lies fueling these people to come after them--and find a way to face them head on"--